Las adaptaciones curriculares para los niños con autismo en el nivel inicial. - Velasco Curay, Angélica Tatiana (2020)
This research work is important since it allowed to know the different curricula necessities, helping to create new and innovative methodological strategies to make curricular adaptions for autism children, it was considered the inclusive educative methods from the curricular approach in the teaching - learning process. Having as general objective to implement the curricular adaptions to guarantee the integral development in children with autism in the Initial level. In a systematic way the scientific method was used for the research, combining the bibliographic research and the field study, besides it was quantitative the same that allowed the data recollection through the use of direct observation token, surveys to executives, teachers and parents, regarding educational behavior of the autism children, the results led us to understanding, description and analysis of the study variables, obtaining as a result the necessity of create new methodological adaption curricular proposals for autism children and in this way take advantage of the benefits that the government offers them contributing to their general well-being, providing tools to the teachers to face the challenges and give a solution to the problems of everyday life strengthening the inclusion process and providing a high education level. Complying with the right and access to the education guaranteeing the quality and equality of opportunities without discrimination and educational exclusion.